APLIKASI SISTEM INFORMASI GEOGRAFIS BERBASIS WEB PENYEBARAN DANA BANTUAN OPERASIONAL SEKOLAH - Hamidi Hamidi (Department of Informatics, Universitas Diponegoro, 2011)
Geographic Information System (GIS) on web mapping form is one of new technology in developing web applications for spatial data processing. This system, is capable of spatial data and attribute data analyzing, thus it makes user easier in using this information system. Nowadays web mapping technology not only used for spatial problems solving, but also for data analyzing. The use of GIS are in the fields of medical, politic, social, electricity, engineering etc. This research was a development of web based GIS for dissemination funding assistance for school operational ( Bantuan Operasional Sekolah = BOS) which this system was made by map server and chameleon for web mapping application. This GIS in dissemination of BOS funds program produces spatial analyzing as dissemination of BOS funding map.